Sliding Mode Controller Design Using Fuzzy Sliding Surface for Flexible Joint Manipulator - AK, AYÇA (TAYLOR & FRANCIS LTD, 2022)
This paper focuses on designing a new robust controller for flexible joint manipulator using time-varying sliding surface. The sliding mode control is thought to be a powerful choice to overcome nonlinear and parametric uncertainties of flexible joint robot manipulators. The basic idea of the proposed control method is based on fuzzifying the sliding surface. Mamdani type fuzzy controller is used for this purpose. The results have demonstrated that the designed control method has superior performance. It is observed that the proposed control algorithm continues to be efficient in the presence of disturbances. In addition, the results are compared with both fuzzy sliding mode control in which the switching control gain was adjusted by fuzzy logic and the classical sliding mode control. It is observed that the method of adjusting the sliding surface with fuzzy logic follows the desired trajectory with less error than other methods. At the same time, the chattering is eliminated by the proposed method.
Keywords: Flexible manipulator; Fuzzy logic; Sliding mode control